Plastid-to-Nucleus Retrograde Signalling during Chloroplast Biogenesis Does Not Require ABI4 - Kacprzak, Sylwia M. (Plant Physiol, 2019)
Multiple abi4 alleles fail to show a deficiency in chloroplast-to-nucleus retrograde signalling indicating that, contrary to contemporary models, ABI4 is not a component of this signalling pathway